COVID-19 and Consumer Financial Vulnerability - Johan Van Ophem (The Central European Review of Economics and Management (CEREM), 2020)
Aim: This paper provides an overview of the impact of COVID-19 on consumer (household) financial vulnerability in the Netherlands in the context of socio-economic developments for households in the period 2008-2016. ~ Design/ research methods: After a discussion of the socio-economic developments for household in the period 2008-2016, financial vulnerability analytics is used to discuss the implications of the published results of two surveys on the impact of COVID-19 on the financial situation of households in the Netherlands (AFM/CPB, NIBUD). ~ Findings: It appears that problems are to be expected in households with uncertain incomes (e.g., flex workers and self-employed), in households with inflexible budgets (with fixed and necessary expenses higher than disposable income), in households that are fragile because of lack of buffers, and in households with a low income for a longer period of time. Some households such as the ones of singles and the young are less able to cope with the financial risks than others. There are lifecycle effects to be noted: the young will have difficulty in finding and keeping jobs, and therefore in making ends meet. ~ Value of research: The analytics and results are of interest and relevant for cross-cultural research in other Western Countries.
Keywords: 330; Corona; COVID-19; financial vulnerability; income decline; unemployment